2017
DOI: 10.1111/ajr.12377
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of vulnerability on perceptions of social cohesion in the context of community resilience to disaster in the Blue Mountains

Abstract: Objective: To assess the impact of network communications, community participation and elements of vulnerability on the perception of social cohesiveness in the Blue Mountains local government area (Blue Mountains LGA). Design: A questionnaire was administered to residents of the Blue Mountains LGA. Econometric analysis of the resulting data was undertaken. Setting: Blue Mountains LGA, Australia. Participants: One thousand one hundred and three residents of the Blue Mountains LGA responded to the questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Service disrupters such as pandemics, floods, droughts and fires not only bring their own mental health demands on communities and workers, 23 but they also put pressure on leadership and organisations 24 . Crises and disasters require rapid deployment and redeployment of personnel and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Service disrupters such as pandemics, floods, droughts and fires not only bring their own mental health demands on communities and workers, 23 but they also put pressure on leadership and organisations 24 . Crises and disasters require rapid deployment and redeployment of personnel and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Like a rudderless ship, a community in recovery will founder without the direction of strong and confident leadership. Community leaders have proved to be an integral part of the recovery of a community from a disaster 17 . They are instrumental in coordinating volunteers, distributing resources and providing support for vulnerable and marginalised community members 2 .…”
Section: Discussionmentioning
confidence: 99%
“…As recovery continues, new social dynamics emerge. If people struggle to communicate their unique needs (to friends, to funding bodies or human service agencies) in this new structure, tensions can arise which may cause further fractures in the community 16,17 . Gordon 15 argues that ‘Unless assistance measures, recovery resources and agencies are integrated into the emerging social infrastructure, their effect will further stress and potentially damage social infrastructure’ (p. 12).…”
Section: Introductionmentioning
confidence: 99%
“…Houston et al [34] identified through a literature review that social media has at least 15 important resilienceenhancing functions from pre-event to post-event (e.g., signaling and detecting disasters, sending and receiving requests for help or assistance, documenting and learning about the disaster events, etc.). Redshaw et al [35] found that the social cohesion index (CSI) was positively associated with both the extent of network communication and the level of community participation, suggesting that enhancing both network communication and community participation will result in higher levels of perception of social cohesion.…”
Section: Social Media In Disaster Researchmentioning
confidence: 99%